Evidence for the Rare Decay Σ+→pμ+μ−; Physical Review Letters; Vol. 120, iss. 22 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M. Marco; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen